Integrasi Pekabaran Injil Ke Dalam Pendidikan Agama Kristen - Malik Bambangan; Charles Ismawan (STT Pelita Dunia, 2022)
Abstract: This study discusses the integration of evangelism into Christian Religious Education. Thus, every Christian Religious Education teacher will be actively involved in his role as a Christian religion teacher. This research is because there is a phenomenon about Christian religious teachers who work only as teachers and do not involve themselves in evangelism. Likewise, the ministry in the church is as if there is a thick barrier. Through this research, it is hoped that Christian religious education teachers can play an active role in spreading the gospel through their teaching methods in schools. The research method used in this preparation is a literature study approach by collecting the views of experts and then compiling them in the form of articles. As a result, it is found that Christian religious education teachers can apply the gospel message in their teaching by using the Bible as the only Word of God. Christian religious teachers can act as evangelists, motivators, facilitators, counselors, and mentors, even shepherds for their students. Abstrak: Penelitian ini membahas tentang integrasi pekabaran Injil ke dalam Pendidikan Agama Kristen. Dengan demikian setiap guru Pendidikan Agama Kristen akan terlibat secara aktif dalam melaksanakan perannya sebagai guru agama Kristen. Tujuan dilakukannya penelitian ini karena ada muncul fenomena tentang guru agama Kristen yang berprofesi hanya sebagai guru saja dan tidak melibatkan diri dalam pekabaran Injil. Demikian juga pelayanan di gereja, seakan terdapat sekat yang tebal. Melalui penelitian ini diharapkan agar para guru pendidikan agama Kristen dapat berperan aktif dalam pekabaran Injil melalui metode pengajaran mereka di sekolah. Metode penelitian yang penulis gunakan dalam penyusunan ini adalah pendektan studi kepustakaan dengan mengumpulkan pandangan para ahli lalu menyusunnya dalam bentuk artikel. Sebagai hasil yang didapatkan bahwa guru Pendidikan agama Kristen dapat menerapkan pekabaran Injil dalam pengajaran mereka. Dengan menggunakan Alkitab sebagai satu-satunya firman Tuhan. Guru agama Kristen dapat berperan sebagai penginjil, motivator, fasilitator, konselor, dan pembimbing, bahkan sebagai gembala bagi peserta didiknya.